Differential response of K(ATP) channels containing SUR2A or SUR2B subunits to nucleotides and pinacidil. - Reimann, F; Gribble, F; Ashcroft, F (2000)
ATP-sensitive K-channels (K(ATP) channels) are the target for K(ATP)-channel openers (KCOs), such as pinacidil and P1075. These channels are formed from pore-forming Kir6.2 and regulatory sulfonylurea receptors (SUR2A in heart and skeletal muscle; SUR2B in smooth muscle). The two isoforms of SUR2 differ only in their final 42 amino acids, a region that includes neither the Walker A and B nucleotide binding motifs nor the proposed KCO binding site, yet channels containing SUR2A or SUR2B respond differently to both nucleotides and KCOs. We explored the basis for this difference by expressing Kir6.2/SUR2A and Kir6.2/SUR2B currents in Xenopus laevis oocytes. Kir6.2/SUR2B but not Kir6.2/SUR2A currents were activated by the Mg-nucleoside triphosphates MgATP and MgGTP, whereas both channel types responded to the diphosphates MgADP and MgGDP. This activation of Kir6.2/SUR2B currents by MgATP explains how the ATP concentration-response curve is shifted to the right in the presence of Mg(2+). In the absence of nucleotide, pinacidil and P1075 activated Kir6.2/SUR2B and Kir6.2/SUR2A currents, but the presence of nucleotide slowed the drug off-rates. In the presence of MgATP, the response to pinacidil reversed approximately 14 times more slowly with SUR2B than SUR2A. The EC(50) for ATP, measured by its ability to slow the pinacidil off-rate, was also approximately 20 times higher for channels containing SUR2A than SUR2B. Our findings suggest that nucleotide binding and/or hydrolysis is enhanced in SUR2B compared with SUR2A, and that the greater KCO-affinities of SUR2B compared with SUR2A may be a consequence of this altered nucleotide handling.